Effectiveness of the Al-Miftah Lil Ulum Method in Reducing Student Boredom in Learning Arabic Grammar - Hasanah, Eva Maulidatul; Akhbar, Khoiril; Azzi, Salma Abid (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
This research examines the success of several students in learning Arabic qowaid (grammar) at Muqaddimatul Akhlaq Islamic Junior High School. While observing Arabic language learning activities, the researcher identified several challenges, including 1) students’ limited understanding of nahwu (Arabic syntax) rules and 2) a monotonous and unengaging learning system. The research aims to: 1) the effectiveness of the Al-Miftah Lil Ulum method in reducing student fatigue in learning Arabic qowaid and 2) whether the Al-Miftah Lil Ulum method improves students’ mastery of Arabic qowaid. This research employs a qualitative descriptive approach, specifically field research, to analyze the implementation of the Al-Miftah Lil Ulum method. Data analysis techniques include domain, taxonomic, componential, and thematic analyses. The findings indicate that implementing the Al-Miftah method at Muqaddimatul Akhlaq Islamic Junior High School has been effective and aligns with the guidelines outlined in the Al-Miftah Lil Ulum method handbook.